2012
DOI: 10.1038/ncomms2274
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of carbon storage in mountainous headwater rivers

Abstract: Published research emphasizes rapid downstream export of terrestrial carbon from mountainous headwater rivers, but little work focuses on mechanisms that create carbon storage along these rivers, or on the volume of carbon storage. Here we estimate organic carbon stored in diverse valley types of headwater rivers in Rocky Mountain National Park, CO, USA. We show that low-gradient, broad valley bottoms with old-growth forest or active beaver colonies store the great majority of above-and below-ground carbon. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
179
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 161 publications
(184 citation statements)
references
References 39 publications
2
179
2
1
Order By: Relevance
“…In this way, fluvially transported organic matter can be explained by soil erosion and sedimentary deposits [27], considering that organic material is mainly discharged from flat watersheds due to their past rainfall changes. Relatively complex, physically-based models have been developed to represent OC mobilization and export from terrestrial sources (e.g., [28,29]). While they provide promising results, the requirement for intensive computation and sophisticated modelling may hinder further applications at large spatial (e.g., regions) or temporal (e.g., future climate scenarios) scales.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, fluvially transported organic matter can be explained by soil erosion and sedimentary deposits [27], considering that organic material is mainly discharged from flat watersheds due to their past rainfall changes. Relatively complex, physically-based models have been developed to represent OC mobilization and export from terrestrial sources (e.g., [28,29]). While they provide promising results, the requirement for intensive computation and sophisticated modelling may hinder further applications at large spatial (e.g., regions) or temporal (e.g., future climate scenarios) scales.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing more specifically on soil organic carbon, the major component of soil organic matter, its storage in alluvial soils may vary as a function of several variables. For instance, the frequency of flooding (Bernal and Mitsch, 2008) and the concomitant deposition of carbon-rich sediments usually lead to an increase in soil organic carbon stocks (Cierjacks et al, 2011;Wohl et al, 2012), either in the humic layer or in the underlying organic matter layers enriched within the profile (Blazejewski et al, 2009;Cierjacks et al, 2010) thus preserving autochthonous organic material (Zehetner et al, 2009). Moreover, vegetation directly influences soil carbon accumulation and consequently soil development by aboveground and belowground inputs (Giese et al, 2000) leading to high spatial heterogeneity in terms of vertical and horizontal SOM distribution (Blazejewski et al, 2009;Drouin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…So the BAU condition in both segments indicated that the total carbon stock stored was estimated at 183,035.7 ton C in 2020 or 9,356.57 ton C deficit from 2012. Carbon storage reduction in the BAU scenarios is also stated in Wohl, Dwire, Sutfin, Polvi and Bazan (2012) that historical changes in riverine complexity have likely reduced carbon storage in mountain's headwater rivers in Rocky Mountain National Park, USA.…”
Section: Carbon Stock and Comentioning
confidence: 97%